2019
DOI: 10.1016/j.triboint.2019.105849
|View full text |Cite
|
Sign up to set email alerts
|

Further understanding of rolling contact fatigue in rolling element bearings - A review

Abstract: Rolling bearings are one of the most widely used components in industrial machinery. If suitably mounted, loaded, lubricated and isolated from contamination, rolling contact fatigue (RCF) is believed to be the most probable mode of failure resulting in subsurface originated failures. Over the past several decades many researchers have studied the failure and microstructural alterations in bearings such as dark etching regions and white etching bands and how operating conditions such as pressure, temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 140 publications
1
47
0
Order By: Relevance
“…When there is a defect point on the outer surface of a rolling bearing, the rolling bearing passes the defect point during operation, which will generate a periodic pulse force to the system. Generally, because the outer ring is fixed, the pulse intensity of each cycle is considered as constant, and the periodic pulse signal presents the law of periodic equal amplitude vibration changes [35]. This section simulates the incipient failure of the rolling bearing outer ring.…”
Section: The Rolling Bearing Outer Ring Fault Simulation Resultsmentioning
confidence: 99%
“…When there is a defect point on the outer surface of a rolling bearing, the rolling bearing passes the defect point during operation, which will generate a periodic pulse force to the system. Generally, because the outer ring is fixed, the pulse intensity of each cycle is considered as constant, and the periodic pulse signal presents the law of periodic equal amplitude vibration changes [35]. This section simulates the incipient failure of the rolling bearing outer ring.…”
Section: The Rolling Bearing Outer Ring Fault Simulation Resultsmentioning
confidence: 99%
“…dark etching regions (DERs) and white etching bands (WEBs), are directly associated with the accumulation of plasticity which in turn related to the applied alternating stress range; the evolution of such Mises stress profile also helps to retard the development of visible microstructural alterations. Recent studies [34,36] have shown that microstructural alterations are governed by the maximum distortion energy yield criteria during multiaxial RCF loadings where subsurface plasticity is governed by equivalent von Mises stresses. Inclusion of deep zone residual stresses with von Mises stress profile can better explain the formation mechanism of such microstructural alterations.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies [32,33] have employed micro-indentation experiments on RCF damage evaluation and reported a gradual increase in material hardness with the linear accumulation of plastic strains. However, they were unable to evaluate the very localised damage of the RCF damaged zone due to the limitation of micro-indenter that only gives an average hardness over the grain [34]. Current research work overcomes that problem with the use of a Berkovich nanoindenter.…”
Section: Introductionmentioning
confidence: 99%
“…With the vigorous development of the machinery industry, rolling bearings have become an important component of rotating machinery and are widely used in generators, gas engines and other kinds of rotating machinery [ 1 , 2 ]. The local fault of rolling bearing will directly affect the normal operation of the whole of the mechanical equipment, so it is important to explore a new fault diagnosis technique.…”
Section: Introductionmentioning
confidence: 99%